2022
DOI: 10.1016/j.esmoop.2022.100406
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of COVID-19 impact on DELAYing diagnostic-therapeutic pathways of lung cancer patients in Italy (COVID-DELAY study): fewer cases and higher stages from a real-world scenario

Abstract: Introduction Coronavirus disease 2019 (COVID-19) has disrupted the global health care system since March 2020. Lung cancer (LC) patients (pts) represent a vulnerable population highly affected by the pandemic. This multicenter Italian study aimed to evaluate whether the COVID-19 outbreak impacted on access to cancer diagnosis and treatment for LC pts compared to pre-pandemic time. Methods Consecutive newly diagnosed LC pts referred to 25 Italian Oncology Departments bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 27 publications
4
44
0
Order By: Relevance
“…A limitation of our study is the inclusion of a small number of patients from a single hospital. Although a study in Italy showed no significant delays from the onset of symptoms to diagnosis or treatment, 7 it was difficult to conclude whether the results of this study have implications for other areas or countries because there are substantial differences in the severity of the pandemic and in medical systems between countries. Further studies involving a larger number of patients in multiple hospitals are needed to confirm diagnostic and treatment delays resulting from the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…A limitation of our study is the inclusion of a small number of patients from a single hospital. Although a study in Italy showed no significant delays from the onset of symptoms to diagnosis or treatment, 7 it was difficult to conclude whether the results of this study have implications for other areas or countries because there are substantial differences in the severity of the pandemic and in medical systems between countries. Further studies involving a larger number of patients in multiple hospitals are needed to confirm diagnostic and treatment delays resulting from the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 62%
“… 5 However, a slight reduction was observed in the number of newly diagnosed lung cancer cases during the pandemic in Italy. 7 One possibility for this difference could be the differential magnitude of pandemic cases between countries. However, it was difficult to explain why the number of patients with SCLC was higher during the pandemic compared with the pre-pandemic period, in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, as a multicenter study carried out from a broad national collaboration [39], it reflects the heterogeneous response to COVID-19 across different levels, including pandemic geographic distribution and local governments' crisis management. More significantly, previous investigations were largely conducted through network comparisons at major risk of inadequacies in reporting high-quality and real-time data from electronic records during the immediate crisis response [40,41].…”
Section: Study's Strengths and Limitationsmentioning
confidence: 99%
“… 8 A slight reduction in newly diagnosed lung cancer cases was observed in 2020 compared to 2019 in several other studies. 28 , 29 , 30 , 31 However, some studies have observed relevant decrease in lung cancer diagnoses 32 , 33 likely due to the disruption of lung cancer screening 34 , 35 , 36 or to the different setting of the study (hospital vs population‐based). Lung cancer screening is not available in Italy.…”
Section: Discussionmentioning
confidence: 99%